Impact of khat production on household welfare in Amhara region of Ethiopia - Ruder, Hanna Lynn (Kansas State University, 2018)
Khat, a lucrative cash crop cultivated in and near the Horn of Africa, is gaining the interest of researchers around the globe. Despite its potential to provide excess income, economic opportunity, and access to technology to those who produce it, the conflicting legal status around the globe causes policy and trade disputes between countries. Research on the impact of khat production on household welfare is sparse. To address this, the purpose of this research is to determine what factors affect the decision to grow khat and subsequently determine the impact of khat production on labor, income, education expenditure, and food security. Data was extracted from a survey conducted in early 2017. A total of 365 households in the Amhara Region of Ethiopia were surveyed. We estimate the factors affecting the decision to grow khat by employing use of two logit models and one linear probability model to calculate marginal effects. We estimate the impact of khat production on labor, income, education expenditure, and food security through propensity score matching. Khat production appears to be adopted by households who are educated and apt to adopt improved technologies. These households are likely to own a donkey, own irrigation, and own more plots than a non-producing household. Practicing seed saving, conservation techniques, and growing more crops decreases the likelihood of growing khat. Regarding impacts, khat production increases on-farm male (41.8%) and female (62.1%) labor and income (41.7%), but decreases education expense (-10.7%), food consumption scores (-15.9%), and number of food shortage months (-16.2%). Overall, khat production uses more labor, generates higher incomes, and decreases food shortage months, but decreases expenditure on education and dietary diversity.
Keywords: Cash crop production; EthiopiaKhat